Absorption characteristics of ilexgenin A and ilexsaponin B1 in human umbilical vein endothelial cells after administration of the total triterpenoid saponins from Ilex pubescens. (5th August 2022) - Qiu, Jingwen; Shang, Xueying; Chen, Bingying; Bai, Rongyu; Wu, Yurong; Wang, Ying; Wan, Xin; Zhou, Yuan; Zhu, Chenchen; Zhang, Ren; Zhang, Juan; Zhao, Zhongxiang; et al.
Abstract: Ilex pubescens is a famous Chinese herbal medicine, frequently used to treat cardiovascular disease in South China. In this study, we aim to explore the absorption properties of ilexgenin A (C1) and ilexsaponin B1 (C3) in vascular endothelial cells after administration of the total triterpenoid saponins from Ilex pubescens (IPTS) and clarify the possible transport mechanisms. A UPLC–qTOF–MS/MS system was used to identify the components in IPTS that could be intracellularly transported by human umbilical vein endothelial cells (HUVECs). Afterwards, a rapid, highly selective and sensitive method was established to simultaneously quantify the concentration of C1 and C3 in HUVECs after administration of IPTS. The results demonstrate that pretreatment with IPTS could promote the survival of HUVECs and reduce the damage caused by TNF‐ α to HUVECs. Among the main 11 components in IPTS, eight components could be absorbed by HUVECs, including seven triterpenoids and one phenolic acid. The uptake of C1 and C3 by HUVECs occurred in a time‐, temperature‐ and concentration‐dependent manner, indicating the participation of passive diffusion and active transportation mechanisms. The two triterpenoid saponins all exhibited rapid absorption and a bimodal phenomenon in their concentration–time profiles, and equilibrium could be achieved after 6 h. Furthermore, C1 and C3 intracellular transportation was regulated by serum proteins, sodium‐dependent glucose transporter 1 and P‐glycoprotein. The current research for the first time demonstrates the in vitro pharmacokinetics characteristics of C1 and C3 in HUVECs lines, which could supply a new way of understanding the treatment of cardiovascular diseases.